Spalling fracture experiments with ceramic bars at elevated temperatures - Najar, J.; Müller-Bechtel, M. (Archives of Mechanics, 1997)
Spalling experiments with alumina bars at temperatures up to 1500°C have been conducted in a new testing apparatus. A slender uninstrumented specimen is loaded by a compressive pulse reflected from its free end. A bridging piece is placed into the transition zone between the instrumented wave-transmitter and the specimen within the furnace. High-temperature corrections are taking into account the drop in the wave velocity and the continuous drop of the impedance in the bridging piece, which results in the incremental reflections of the pulse. The results of the experiments indicate that the decay of the strength with the increase of the temperature up to 1500°C is much stronger than that anticipated in preliminary tests. The observations can be interpreted within a continuum damage model.